Student responses to a reflexive course evaluation. Issue 6 (1st November 2016) - Erikson, Malgorzata; Erikson, Martin G.; Punzi, Elisabeth
Abstract: Simple surveys are the predominant tool for course evaluations in most universities, but their validity has been questioned. They have been criticized for being a ritual way of complying with administrative regulations rather than a way of improving educational quality. Moreover, there is often a focus on student satisfaction, where the complexity of learning processes and the development of learner identities are lost. As an alternative approach, a qualitative course evaluation was tested that consisted of a single question: What could have been done in this course in order to better support your learning? Twenty-one second-year psychology students completed the evaluation at the end of a course. They provided rich answers describing learning activities and communication, and they described both teachers and students as agents. Going beyond merely reporting possible improvements, the students saw their learning processes in a context of academic demands and social mechanisms. It is argued that qualitative course evaluations can provide information about students' understanding of their own learning that is difficult to uncover in a traditional survey. It is concluded that qualitative course evaluations would support the development of a student learner identity and help create a role for students as co-producers of knowledge.